2015
DOI: 10.3390/molecules200712946
|View full text |Cite
|
Sign up to set email alerts
|

Sumac Silver Novel Biodegradable Nano Composite for Bio-Medical Application: Antibacterial Activity

Abstract: Abstract:The development of reliable and ecofriendly approaches for the production of nanomaterials is a significant aspect of nanotechnology nowadays. One of the most important methods, which shows enormous potential, is based on the green synthesis of nanoparticles using plant extract. In this paper, we aimed to develop a rapid, environmentally friendly process for the synthesis silver nanoparticles using aqueous extract of sumac. The bioactive compounds of sumac extract seem to play a role in the synthesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Therefore it can be supposed that these compounds like flavonoid, tannins and other phenolic compounds acts as the capping agent in the formation of gold nanoparticles which similarly help in the stabilization of nanoparticles at physiological condition 32 . Similar result was also reported in our pervious study for synthesizing of silver nanoparticles 33 .…”
Section: Ftir Analysissupporting
confidence: 92%
“…Therefore it can be supposed that these compounds like flavonoid, tannins and other phenolic compounds acts as the capping agent in the formation of gold nanoparticles which similarly help in the stabilization of nanoparticles at physiological condition 32 . Similar result was also reported in our pervious study for synthesizing of silver nanoparticles 33 .…”
Section: Ftir Analysissupporting
confidence: 92%
“…This pattern clearly revealed that the AgNPs by green method are nanocrystalline in nature. In present paper, the results are in agreement with different reports that investigated the cubic nature of phyto-synthesised AgNPs [23].…”
Section: Synthesis and Characterisation Of Agnpssupporting
confidence: 93%
“…The range of microbicidal properties of Ag NPs is wider than that of antibiotics, and the appearance of resistant bacteria such as MRSA is rare in Ag NP-based materials [115]. The combination of various materials with Ag NP-based materials has been studied [116,117,118,119]. The production of wound dressings and medical catheters coated with Ag NPs has been investigated.…”
Section: Other Medical Applicationsmentioning
confidence: 99%